Applying the water safety plan to water reuse: towards a conceptual risk management framework. Issue 5 (11th August 2015) - Goodwin, D.; Raffin, M.; Jeffrey, P.; Smith, H. M.
Abstract : The Water Safety Plan (WSP) is receiving increasing attention as a recommended risk management approach for water reuse through a range of research programmes, guidelines and standards. Abstract : The Water Safety Plan (WSP) is receiving increasing attention as a recommended risk management approach for water reuse through a range of research programmes, guidelines and standards. Numerous conceptual modifications of the approach – including the Sanitation Safety Plan, the Water Cycle Safety Plan, and even a dedicated Water Reuse Safety Plan – have been put forward for this purpose. However, these approaches have yet to encapsulate the full spectrum of possible water reuse applications, and evidence of their application to reuse remains limited. Through reviewing the existing evidence base, this paper investigates the potential for adapting the WSP into an approach for water reuse. The findings highlight a need for the management of risk to reflect on, and facilitate the inclusion of, broader contexts and objectives for water reuse schemes. We conclude that this could be addressed through a more integrated approach to risk management, encapsulated within an overarching risk management framework (adapted from the WHO's Framework for safe drinking water) and operationalised through the Water Reuse Safety Plan (WRSP). We also propose that the WRSP should be based on modifications to the existing WSP approach, including an increased emphasis on supporting communication and engagement, and improvements in decision support mechanisms to better account for uncertainty, risk interactions and risk prioritisation.